Pengaruh Pendidikan Kesehatan terhadap Tingkat Pengetahuan tentang Imunisasi Polio dan Pentabio pada Ibu yang Memiliki Anak (Usia 0-6 Bulan) di Wilayah UPTD Puskesmas Kayon Palangka Raya: The Effect of Health Education on the Level of Knowledge of Polio and Pentabio Immunization in Mothers who Have Children (Ages 0-6 Months) UPTD Puskesmas Kayon Palangka Raya - Indriani, Indriani; Natalia, Vita; Sari, Wika (Jurnal Surya Medika (JSM), 2022)
Background Polio immunization is used to prevent poliomyelitis disease that can cause paralysis in infants. The disease is caused by a poliomyelitis virus that enters through the food, breeds in the gastrointestinal lymph nodes, then spreads through the blood to the nervous system, resulting in paralysis or lifelong disability. Immunization of combined pentabio DPT-HB and Hib vaccine. Pentabio immunization prevents certain diseases, such as diphtheria, whooping cough, tetanus, hepatitis B, meningitis, and pneumonia caused by Hib bacteria (Haemophilus influenza type b). The phenomenon that occurred at Kayon Health Center when interviewed, there are still many mothers who are less aware of polio and pentabio immunization. Objectives The purpose of this study was to determine the effect of health education on the level of knowledge about polio immunization in mothers who have babies (aged 0-6 months) in the UPTD Work Area of the Kayon Health Center Palangka Raya. The design used in this study uses a pre-experimental research design with a "one group pre-test and post-test design. Sampling using purposive sampling and a sample of 15 respondents mothers who have a baby (age 0-6 months). The data were collected using questionnaires, then analyzed using a non-parametric statistic test of the Wilcoxon sign tank test. The result of statistical test analysis using the Wilcoxon test above got a P-Value of 0,003 <0,05, so health education influences the mother's knowledge level about polio immunization and pentabio at baby 0-6 months. In conclusion, after being given health education, respondents have an increased level of knowledge. It is expected that the research can provide information about the influence of health education on the level of knowledge about immunization of polio and pentabio in mothers who have babies (ages 0-6 months) to increase mothers' knowledge in the importance of polio and pentabio immunization in children.